Suspension Two-Layered Blood Flow Through a Bell Shaped Stenosis in Arteries - Amit Medhavi (Applied Bionics and Biomechanics)
The present study concerns with the effects of the hematocrit and the peripheral layer on blood flow characteristics due to the presence of a bell shaped stenosis in arteries. To account for the hematocrit and the peripheral layer, the flowing blood has been represented by a two-layered macroscopic two-phase (i.e., a suspension of red cells in plasma) model. The expressions for the flow characteristics, namely, the velocity profiles, the flow rate, the impedance, the wall shear stress in the stenotic region and the shear stress at the stenosis throat have been derived. The quantitative effects of the hematocrit and the peripheral layer on these flow characteristics have been displayed graphically and discussed briefly.